ANALISIS HUBUNGAN TIPOGRAFI DENGAN CITRA PRODUK PADA LOGO MEREK "PIZZA HUT" - bilqis agneza herwanda; Gadis Cantik Bunga Tunjungwangi (Jurnal Ilmiah Wahana Pendidikan, 2023)
A logo is a characteristic of a culture of corporate behavior, personality, and attitude that is validated as identity. The logo contains elements in visual communication such as shape, color and typography. Typography is the technique of selecting letters and text used in graphic design to make visuals readable and interesting to see, and is applied to typography in a product logo. Some logos are well represented so that the product image or brand image on the product has more value in the consumer's memory, including the logo on the pizza hut product included in the typographic logo. The purpose of this analysis is to identify the typographical relationship in the "pizza hut" logo with the brand image that the product has. In this analysis, qualitative methods are used. The results of literature studies are the source of data